FIRST GENERATION REPRODUCTIVE PERFORMANCE AND SECOND GENERATION LARVAL PRODUCTION ON THE DOMESTICATED TINFOIL BARB, Barbonymus schwanenfeldii (BLEEKER, 1854) - Kusmini, Irin Iriana; Cahyanti, Wahyulia; Gustiano, Rudhy; Sundari, Sri; Iskandar, Andri; Radona, Deni; Kurniawan, Kurniawan; Prakoso, Vitas Atmadi; Putri, Fera Permata; Arifin, Otong Zenal; Subagja, Jojo; Kristanto, Anang Hari; Prihadi, Tri Heru; Mulyasari, Mulyasari; Yosmaniar, Yosmaniar; Subaryono, Subaryono (Indonesian Aquaculture Journal, 2023)
Tinfoil barb, Barbonymus schwanenfeldii (Bleeker, 1854), is a potential freshwater fish for Indonesian aquaculture. Before widely used, the candidate needs to be evaluated. This research aimed to evaluate the reproductive performance of the first generation (G1) and larval performance of the second generation (G2) of domesticated tinfoil barb. A total of 68 female and 24 male broodstocks were selected for the artificial breeding program. The gonadal maturity test was carried out by canulating the eggs every month. Before spawning, GnRHa hormone was injected into the dorsal area (0.5 mL/kg for female and 0.2 mL/kg for male). Fecundity, fertility rate, hatching rate, embryogenesis, and larvae ontogeny were recorded. The results showed that the first matured G1 males of tinfoil barb were at the standard length of 16.01 ± 1.18 cm, while females at 15.79 ± 1.23 cm. The mature broodstock indicated by the gonad maturity stage III and IV confirming higher estradiol concentration (above 400 pg mL-1). The fecundity of two mature broodstock-sized of 217.2 g and 197.3 g were 12,495 and 15,782 eggs, respectively. The spawning season of G1 tinfoil barb was in October and November (rainy seasons). The fertilized eggs latency time was 10 hours 44 minutes at 25°C and hatched after 23 hours 7 minutes. The fertility rate was 96.96 % and the hatching rate was 95.16 %. The survival rate of G2 normal larvae was 100 % at three days of the rearing period. The G2 larvae production in this experiment provides an excellent opportunity for fish diversification both for aquaculture and restocking.